Pengaruh Model Pembelajaran Contextual Teaching and Learning terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Materi Perkalian - Melina Dewi Wulandari; Sarafuddin Sarafuddin (Departement of Mathematics Education, 2023)
The pe of this study was to determine whether there was an effect of the Contextual Teaching and Learning Learning Model on Student Learning Outcomes in Mathematics Subject Multiplication Material Class III SD Negeri Nayu Barat I Surakarta. This type of research is is quantitative research using pre-experimental methods with a one group pretest-posttest research design. In this study, the population used was class III students at SD Negeri Nayu Barat I Surakarta for the 2021/2022 academic year with a total of 28 students. The sample used in this study used the entire population of class III students at SD Negeri Nayu Barat I Surakarta for the 2021/2022 academic year with a total of 28 students. The sampling technique used is saturated sampling. Instrument trials use validity and reliability tests. Data collection techniques used in this study were observation, testing and documentation. The data analysis technique in this study was a prerequisite test using the Kolmogrov Smirnov formula as an initial analysis, and hypothesis testing using a paired t-test. The results of the study obtained a mean of 61.67, a median of 60.00, a mode of 52, a standard deviation of 8.295 while the results of the posttest mean 78.428, median 78, mode 83, standard deviation of 8.295. Judging from the results of the pretest and posttest there is an increase in student learning outcomes.